Visual Predictive Control Scheme for a Mobile Robot Navigating in a Cluttered Environment - Durand-Petiteville, Adrien; Cadenat, Viviane (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
This work focuses on the use of Visual Predictive Control to drive a mobile robot in a cluttered environment. To efficiently and safely achieve the navigation task, one proposes to modify a classical VPC scheme by (i) relaxing some control input boundaries to extend the feasibility set and guarantee the stability, (ii) adding obstacle constraint over the pieces of trajectory, and (iii) modifying the calculated solution to avoid local minima. Simulated results highlight the efficiency of the proposed approach.